WHERE ARE WE? LECTURERS RECEPTIVITY OF SERVICE LEARNING IN NIGERIA - Gbadamosi, Tolulope Victoria (PEOPLE: International Journal of Social Sciences, 2018)
Universities in Nigeria are established to perform three functions- teaching, research and community service. In spite of the establishment of several government and private-owned universities in Nigeria, most of these tertiary institutions have been criticised for not meeting the objectives of their establishment. This is because gaps between the gown and the town exist to the extent that the functionality of the education provided and the relevance of the certificates awarded to the society are being questioned. However, service learning was one of the ways used to bridge the gaps between the universities and communities in some of the developed and developing countries. This study therefore examined the extent to which lecturers incorporate service learning into teaching learning process. The study adopted mixed research design. Three research questions were posed for the study. Validated Service learning Structure Interview Schedule (r= 0.826) was administered to One hundred and fifty lecturers selected from three Universities in Southwest, Nigeria using multi stage sampling technique. The data collected was analysed using descriptive statistic and content analysis. The results and implications of the findings were discussed while recommendations were also made.